Educational software tool for decoupling control in wind turbines applied to a lab‐scale system. Issue 3 (10th February 2016) - Fragoso, Sergio; Ruz, Mario L.; Garrido, Juan; Vázquez, Francisco; Morilla, Fernando
ABSTRACT: This paper presents an educational software tool, called wtControlGUI, whose main purpose is to show the applicability and performance of different decoupling control strategies in wind turbines. Nowadays, wind turbines are a very important field in control engineering. Therefore, from an educational point of view, the tool also aims to improve the learning of multivariable control concepts applied on this field. In addition, wtControlGUI allows for testing and controlling of a lab‐scale system which emulates the dynamic response of a large‐scale wind turbine. The designed graphical user interface essentially allows simulation and experimental testing of decoupling networks and other multivariable methodologies, such as robust or decentralized control strategies. The tool is available for master degree students in control engineering. A survey was performed to evaluate the effectiveness of the proposed tool when it is used in educational related tasks. © 2016 Wiley Periodicals, Inc. Comput Appl Eng Educ 24:400–411, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21718